2016
DOI: 10.1128/msphere.00176-16
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Bactericidal Activity Is Countered by Maintaining pH Homeostasis in Mycobacterium smegmatis

Abstract: Since the discovery of antibiotics, mortality due to bacterial infection has decreased dramatically. However, infections from difficult to treat bacteria such as Mycobacterium tuberculosis and multidrug-resistant pathogens have been on the rise. An understanding of the cascade of events that leads to cell death downstream of specific drug-target interactions is not well understood. We have discovered that killing by several classes of antibiotics was stopped by maintaining pH balance within the bacterial cell,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 50 publications
6
52
3
Order By: Relevance
“…A hallmark of metabolically active, non-replicating states is the development of phenotypic tolerance to antibiotics and stress [9,12,34,35]. A role of acidic pH in promoting antibiotic tolerance by preventing cytosolic alkalinization has been previously shown in Mycobacterium smegmatis [36]. The sensitivity of Mtb to isoniazid, rifampin, and the detergent sodium dodecyl sulfate (SDS) was measured to test whether acid growth arrest was associated with phenotypic drug or stress tolerance.…”
Section: Resultsmentioning
confidence: 99%
“…A hallmark of metabolically active, non-replicating states is the development of phenotypic tolerance to antibiotics and stress [9,12,34,35]. A role of acidic pH in promoting antibiotic tolerance by preventing cytosolic alkalinization has been previously shown in Mycobacterium smegmatis [36]. The sensitivity of Mtb to isoniazid, rifampin, and the detergent sodium dodecyl sulfate (SDS) was measured to test whether acid growth arrest was associated with phenotypic drug or stress tolerance.…”
Section: Resultsmentioning
confidence: 99%
“…Under anoxia, nitrate frequently participates in anaerobic respiration as the terminal electron acceptor and can potentiate antibiotic killing [33]; it is not yet known if nitrate and other terminal electron acceptors also generate toxic metabolic byproducts that contribute to antibiotic death processes. Cellular respiration likely affects antibiotic efficacy due to its roles in metabolism and energy production, but may also contribute to lethality by facilitating drug import [37,71] or stimulating intracellular alkalization [72]. Collectively, these studies implicate respiratory activity as an important mediator of the lethal processes induced by antibiotics.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…In this strain, we were unable to isolate spontaneous resistance mutants after several attempts plating at 4xMIC (observed frequency of resistance <4.8 x 10 −10 ). Recently, it has been proposed that antibiotic-induced bacterial cell death can be partially attributed to an imbalance in proton homeostasis across the inner membrane 32,33 . Moreover, previous work suggested that the antifungal activity of metergoline against Candida krusei was due to depolarization of the mitochondrial membrane potential and induction of reactive oxygen species 34 .…”
Section: Resultsmentioning
confidence: 99%